Application of an improved genetic algorithm fuzzy PID control algorithm for greenhouse - Hua, Xiao; Yunde, Shen; Yidong, Wang; Haofeng, Qiu; Mingge, Wu (2024 4th Asia-Pacific Conference on Communications Technology and Computer Science (ACCTCS), 2024)
Aiming at the characteristics of nonlinearity, time-varying and hysteresis of greenhouse environmental factors, it is proposed a fuzzy PID control algorithm which is optimized according to the revised heredity algorithm. According to the commonly used intelligent control method of greenhouse, the enhanced hereditary operation algorithm was adopted to optimize the fuzzy control, which effectively solves the shortcomings of fuzzy PID over-reliance on expert experience and lack of dynamics. Through the simulation of greenhouse environment temperature, the feasibility of the proposed modified inherited algorithm to oxidize fuzzy PID algorithm was verified. The maximum deviation of the algorithm is 1.2%, and the response time is 826s, which is far less than the traditional control method. It has produced favourable outcome in terms of greenhouse monitoring, which has improved the level of greenhouse monitoring.